Pengaruh etos kerja, dan penilaian kerja terhadap pengembangan karir karyawan PT. RIM Tour dan Travel Gorontalo - Roydah Gani (Gorontalo Management Research, 2018)
ROYDAH GANI, 2018 The aim in this study was to analyze the effect of the work ethic, and appraisal of the career development of employees at PT. RIM Tour And Travel Gorontalo. The data collection techniques used is to use direct observation is directly by visiting the source of the data that the object of research to make observations, interviews with the respondents in order to complete the necessary data, documentation and research libraries.Data analysis was performed in the data processing that quantitative analysis to analyze the influence of motivation and job rotation on the performance of employees at PT. RIM Tour And Travel Gorontalo. which concluded: namely Work Ethics and Work Assessment proven positive effect on employee career development variables and variable most dominant influence on employee career development is variable Work Assessment.